Rancang Bangun Sistem Kunci Kontak Sepeda Motor Berbasis Internet of Things Menggunakan NodeMCU Dan GPS - Teten Dian Hakim; Juang Zidqi Adhi Pratama; Abdul Kodir Al Bahar (JURNAL ELEKTRO, 2025)
The increasing number of motorcycles is one of the factors in the increase in motorcycle theft crimes, a vehicle thief usually uses his own T-shaped key to damage the mechanical system of the ignition lock on a motorcycle vehicle. This research was organized to be a solution in solving the problem of motorcycle theft by designing a motorcycle ignition control system based on IoT using NodeMCU and GPS. Based on the results of the study, it shows that the IoT-based ignition lock control system is able to work optimally in line with what is expected, namely using the Telegram application to activate the relay which makes the NO relay pin connected so that the electrical system in the ignition lock is connected and deactivates the relay which makes the NO relay pin open again so that the electrical system in the ignition lock is disconnected with a response time of ± 15 seconds and ± 16 seconds to get a notification message that the command was successfully executed, and when the relay is inactive if the SW-420 sensor detects vibration, it will immediately send a warning message notification to the Telegram application that the vehicle is in motion. The Telegram application can also find out the location of the vehicle with the help of GPS embedded in the tool that has been made